Geneza intertekstualnosti, poststrukturalizem in slovenska teoretska "neoavantgarda" - Juvan, Marko (Primerjalna književnost, 1999)
The genesis of intertextuality, post-structuralism and the Slovene " neo avant-garde" theory. - The treatise examines the main contexts in which, from 1966 to 1974, Kristeva employed intertextual and interdisciplinary aspects to develop the notion of intertextuality: sociožcritical semiotics, the deconstruction of the sign and structure, post-modernist aesthetics of citations, Bakhtinian dialogism and "metalinguistics" and Saussure's anagrams. Intertextuality originally functioned as a symptom of an institutional crisis in the humanities and was a sign of the transitions and divisions between structuralism and post-structuralism, and also between the modern and post-modern periods. Through the context of early poststructuralism, from the "revolutionary" year of 1968 to the mid 'Seventies, intertextuality also influenced Slovene neo avant-garde art (Ludism) and the semiotic theory of the younger generation, particularly that of S. Žižek.
Keywords: Kristeva, Julia; Žižek, Slavoj, 1949-; literarna veda; literary science; semiotics; semiotika; poststrukturalizem; intertekstualnost; Intertextuality; slovenska literarna veda